Adaptive winding pin and hooking capacity model for coreless filament winding. (January 2023) - Mindermann, Pascal; Gresser, Götz T
Coreless filament winding is a manufacturing process used for fiber-reinforced composites, resulting in high-performance lightweight lattice structures. Load transmission elements, which are assembled from commercially available standardized parts, often restrict the component design. A novel adaptive winding pin was developed, which is made by additive manufacturing and can therefore be adjusted to specific load conditions resulting from its position within the component. This allows to decouple the fiber arrangement from the winding pin orientation, which allows a fully volumetric framework design of components. A predictive model for the pin capacity was derived and experimentality validated. The hooking conditions, pin capacity, and occupancy were considered in the creation of a digital design tool.